Kurikulum “Merdeka Belajar-Kampus Merdeka” di PBA UNSIQ Jawa Tengah - Rifqi Aulia Rahman; Chairani Astina; Nurul Azizah (Taqdir, 2021)
This research departs from the problem of developing the Merdeka Belajar-Kampus Merdeka (MB- KM) curriculum in the PBA UNSIQ which considers the values of local wisdom, in addition to the principles of humanistic ethics in the form of learning freedom to choose competencies and subjects, according to student interest. From several studies related to the development of the MBKM that has been written, there is no research result that examines the development of the MBKM by considering the basic idea to balance local wisdom values and humanistic ethics principles that seem dualistic. This study more specifically discusses the study program's efforts to recondition two opposing value ideas with alternative curriculum development formats. This research used a descriptive qualitative approach, with a literature study, namely the documentation of the results of the development of the MBKM for the PBA UNSIQ. The results showed that the MBKM at PBA UNSIQ has been designed by paying attention to two ideas of humanistic ethics and local wisdom values. This is evidenced in the study program decisions to choose format and structure of the curriculum, design of the learning outcomes of each course, placement of courses, and allocation of credits in each semester